THE NEW LAW OF UKRAINE «ON HIGHER EDUCATION»: DISCUSSION ASPECTS OF THE SCIENCE THESAURUS - Sysoieva, Svitlana O. (Educological discourse, 2015)
The article studies the problem of scientific thesaurus formation of competency oriented higher education. Here are analyzed the basic concepts included in the new Law on Higher Education of Ukraine (2014). It is shown that during the implementation of the Bologna process in Ukraine thanks to the efforts of scholars and practitioners a basis for implementing competence building approach and curriculum based on competencies have been created. The need for harmonization of training models at the national level with the requirements of European higher education to develop a common understanding of the content of qualifications at the bachelor’s and master’s degrees in terms of learning outcomes were actualized in Ukrainian studies whose purpose was to develop different models of competences. It is stressed here that the importance of such studies and documents that are being developed with their account, has adequate interpretation of the meaning of concepts according to the meaning of the concepts of national pedagogical area.